Justificação por graça e fé. 10 anos de assinatura da “Declaração Conjunta sobre a doutrina da justificação”: Ensaio de um balanço crítico em perspectiva protestante - Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2010)
The present article, which preserves its original characteristic of “lecture”, presents a brief retrospective and a critical balance of the discussions happening in the last 10 years about the Joint Declaration on the Doctrine of Justification, from a Lutheran perspective. The author highlights the discussions concerning the normativeness of the Joint Declaration and the implications on the addition of the World Methodist Council to it. He emphasizes, in special, the topics that, despite agreements obtained, remain controversial, such as, the question on the interpretation of the expression “simul iustus et peccator”, the obfuscation of the f inal judgment perspective and the dilution of emphasis found in the Lutheran Reformation. The author concludes emphasizing that the continuity on the debates about the Joint Declaration keeps necessary and it’s an ecumenical imperative. On the second part of the article, the author presents a synthesis of the primary aspects of the Lutheran doctrine on justification that he judges central to the present discussion.